Technical Planning of Drainage Channels on Gatot Subroto Road, Banjarmasin Eastern District - Khaliq, Abdul; Muhlis, Adriani; Fakhrrurrazi; Rosandi, M.Hairil (PT FORMOSA CENDEKIA GLOBAL, 2024)
Floods are a frequent disaster in Indonesia, particularly during the rainy season. To prevent damage, efforts are being made to improve drainage channels that can accommodate rainwater wells. However, water congestion in Gatot Subroto Road, Banjarmasin Eastern District, and Banjarmachin City along drainage channels is observed due to blockages or storage. A study aimed to determine rainfall leakage on the main channel on Gatot Subroto road using direct field observation, data collection, and processing. The study found that the main channel, with a capacity of 4,8502 m3/dt, can accommodate rain spills